Philosophical speculation in traditional Chinese music - Fan, Yifan (2024)
Chinese civilization has always been known as the civilization of rituals and music, with music playing a significant role throughout the dynasties. The development of Chinese traditional music cannot be separated from the injection of various philosophical ideas and social consciousness. Whether it is the ritual music system of the Zhou Dynasty, the Hundred Schools of Thought during the Warring States period, the metaphysical discussions of the Wei and Jin Dynasties, or the Buddhist philosophy of the Han and Tang Dynasties, each era has played an important catalytic role in the formation of the aesthetic theory of Chinese traditional music. This article summarizes the historical developmental process of Chinese traditional music culture. It also analyzes the construction process of the aesthetic philosophy of Chinese traditional music from the perspectives of the three major philosophical schools: Confucianism, Buddhism and Taoism. These three schools have had the most profound impact on Chinese traditional music.